2019
DOI: 10.1016/j.ctro.2018.10.004
|View full text |Cite
|
Sign up to set email alerts
|

The FGF1/CPP-C chimera protein protects against intestinal adverse effects of C-ion radiotherapy without exacerbating pancreatic carcinoma

Abstract: Graphical abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…Interestingly, they have suggested the tumor suppressor role of FGF14 in colorectal cancer [29]. Of note, a recent study reported that FGF12 (the homologue of FGF14 [30]) have a malignancy-inhibitor effect on pancreatic cancer cell lines [31]. Two most recent studies reported that FGF14 overexpression leads to tumor suppressive effects in lung adenocarcinoma and nasopharyngeal carcinoma [32,33].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, they have suggested the tumor suppressor role of FGF14 in colorectal cancer [29]. Of note, a recent study reported that FGF12 (the homologue of FGF14 [30]) have a malignancy-inhibitor effect on pancreatic cancer cell lines [31]. Two most recent studies reported that FGF14 overexpression leads to tumor suppressive effects in lung adenocarcinoma and nasopharyngeal carcinoma [32,33].…”
Section: Discussionmentioning
confidence: 99%
“…It has been well-documented that aFGF plays an important role in wound healing (Zheng et al, 2015;Hota et al, 2018;Wang et al, 2018;Kawano et al, 2019). Compared to the lyophilized rh-aFGF currently on the market, the rh-aFGF-loaded carbomer hydrogel has the advantage of increased drug intake and enhanced bioavailability, providing the wound with a "wet healing environment" and avoiding secondary contamination (Hui et al, 2018b).…”
Section: Discussionmentioning
confidence: 99%